1984
DOI: 10.1111/j.1365-2230.1984.tb00859.x
|View full text |Cite
|
Sign up to set email alerts
|

ACTH versus prednisone and placebo in herpes zoster treatment

Abstract: Summary The effect of ACTH (Synacthen‐depot®) versus prednisone and placebo in the treatment of herpes zoster (HZ) was studied in a controlled clinical trial comprising 60 consecutive patients. The treatment groups were comparable regarding sex, age and pre‐entry symptom duration. The skin changes, patients' pain scores and the consumption of analgesics were monitored. Regarding objective symptoms and the development of postherpetic neuralgia there was no difference between the two treatment groups and placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 12 publications
0
19
0
2
Order By: Relevance
“…The risk of PHN and the intractability of pain increases with age. Few children have PHN, whereas 27%, 47%, and 73% of untreated adults over 55, 60, and 70 years of age, respectively, develop PHN (9,12,13). Pain lasting more than 1 year has been reported in 4%, 22%, and 48% of patients less than 20, more than 55, and more than 70 years of age, respectively (8,9).…”
Section: Herpes Zostermentioning
confidence: 99%
“…The risk of PHN and the intractability of pain increases with age. Few children have PHN, whereas 27%, 47%, and 73% of untreated adults over 55, 60, and 70 years of age, respectively, develop PHN (9,12,13). Pain lasting more than 1 year has been reported in 4%, 22%, and 48% of patients less than 20, more than 55, and more than 70 years of age, respectively (8,9).…”
Section: Herpes Zostermentioning
confidence: 99%
“…In contrast in the results of these studies, 2 Danish studies [61,62] dismissed the use of corticosteroids in herpes zoster based on their results. The first study of 60 patients by Clemmensen and Anderson [61] showed no effect of corticosteroids on healing in the younger population studied (average age 56) and found no significant difference in the number of patients with pain between the corticosteroid group and placebo at 6 weeks. The second study, by Esmann et al, [62] consisted of 78 patients over 60 years old who were all treated with aciclovir.…”
Section: Corticosteroidsmentioning
confidence: 83%
“…[5][6][7][8][9][10][11][12][13] Conclusions from these studies are severely limited, however, due to uncontrolled study design, small sample sizes, variable agents and doses used, and failure to report statistical analysis of the results. In addition, nearly all of the studies excluded patients with comorbid diseases such as hypertension and diabetes mellitus, which are potentially exacerbated by corticosteroids.…”
Section: Clinical Trialsmentioning
confidence: 99%